2011
DOI: 10.1177/1049732311407078
|View full text |Cite
|
Sign up to set email alerts
|

Care Transition Experiences of Spousal Caregivers

Abstract: The purpose of this study was to develop a theoretical framework about caregivers' experiences and the processes in which they engaged during their spouses' transition from a geriatric rehabilitation unit to home. We used a constructivist grounded theory methodology approach. Forty-five interviews were conducted across three points in time with 18 older adult spousal caregivers. A theoretical framework was developed within which reconciling in response to fluctuating needs emerged as the basic social process. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 70 publications
(88 reference statements)
1
40
0
Order By: Relevance
“…It is important, therefore, that, in developing resilience, carers come to terms with or reconcile the dissonance between their past and present relationships and roles (Byrne et al . 2011). Caring also imposes a financial burden on carers in the current study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is important, therefore, that, in developing resilience, carers come to terms with or reconcile the dissonance between their past and present relationships and roles (Byrne et al . 2011). Caring also imposes a financial burden on carers in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…These measures are particularly important as a decline in their personal well-being has undesirable implications for the continuation of their caring role (Byrne et al . 2011). Carers in the present study engage in various forms of physical activity, such as walking and dancing, and participate in recreational activities such as hobbies and occasional holidays.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have also identified that family caregivers are often required to instigate and direct communication with health care providers [12,25,43,73]. A foreseeable problem with this approach is that family caregivers needs and roles change throughout care transitions [74,75]. One study that focused on care transitions from hospital to home, described that family caregivers were less aware of their information needs while the patient was in the hospital, however, after discharge the family caregivers realised that they were missing essential knowledge required to carry out their role [74].…”
Section: Discussionmentioning
confidence: 99%
“…A foreseeable problem with this approach is that family caregivers needs and roles change throughout care transitions [74,75]. One study that focused on care transitions from hospital to home, described that family caregivers were less aware of their information needs while the patient was in the hospital, however, after discharge the family caregivers realised that they were missing essential knowledge required to carry out their role [74]. This demonstrates that there are potential harms of relying on family caregivers to elicit information from health care providers based on their perceived needs.…”
Section: Discussionmentioning
confidence: 99%